Fainting in children: Syncope or Seizure - Saengpattrachai, Montri (The Bangkok Medical Journal, 2012)
OBJECTIVES: The purpose of this study was to identify the etiologies and to assess the diagnostic usefulness of electroencephalogram (EEG) study in children with fainting. MATERIALS AND METHODS: A retrospective review was conducted at the Bangkok Child Health Center, Bangkok Hospital. Fulfilled criteria enrolled pediatric population under 18 years of age with history of fainting or syncope-like attacks who had completed cardiologic and neurologic work up including chest x-ray, electrocardiogram (ECG), echocardiogram, a standard 24 hours Holter monitoring, Tilt-table testing and at least one standard EEG recording. RESULTS: Fainting in children is predominant in girls. Seizure or epilepsy is the second most common etiology (12.5%) preceded by syncope (77.5%) either reflex syncope, orthostatic syncope or that which is cardiac in origin. Our study demonstrated a greater yield of EEG study in identifying causes of fainting than other previous studies. CONCLUSION: Obtaining a detailed illness and witness account is of cardinal importance and very helpful in determining the etiology of fainting. Proper investigations should be tailored to individual patients. EEG recording plays a significant role in patients with historical uncertainty or those with a history strongly suggestive of seizures.